Which equation demonstrates the opposite of a sum property?


A.
(22 + 10) + 3 = (10 + 22) + 3


B.
–5 + 13 = 13 + (–5)


C.
(12 + (–4)) + 14 = 12 + ((–4) + 14)


D.
–(–6 + 17) = 6 + (–17)

Respuesta :

Answer: Choice D which is -(-6 + 17) = 6 + (-17)

A sum is the result of adding two numbers. It doesn't matter if those numbers are positive or negative. In choice D, we start with -6 and 17 which add to -6+17. Then we apply a negative sign to that entire thing to take the complete opposite to get -(-6+17)

The negative sign is distributed through to each term. Whatever was negative turns positive, or vice versa. So -6 turns to +6 or just 6, and 17 becomes -17. That explains how your teacher got 6 + (-17).